Ecologicals and culture concepts in post-disasters housing design in Yogyakarta - Lucky Prasetyo; Rumiati Rosaline Tobing; Hartanto Budiyuwono (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2018)
Post-disaster housing is usually designed with a design that considers only the rapidity of development and cost efficiency without thinking of local cultural and environmental conditions of an area. If this happens continuously, then the local architecture which is a container of local culture and the form of community response to the surrounding environment will slowly be threatened to disappear along with the disaster, which will then be replaced by almost uniform shelter in all places. This study aims to identify ecological and cultural concepts on post-disaster residential design in Ngibikan village that successfully responds to the needs of its inhabitants and blends with the lives of its people. The method used is descriptive qualitative method to explore the concept of ecology and culture on the design in Ngibikan village. Based on the results of the research, it is found that the application of ecological and cultural concepts in the design of post-disaster residential design in Ngibikan village also influenced the success of the design in responding to the needs of the residents and responding to the natural conditions. It is expected that the post-disaster reconstruction process in Ngibikan village can serve as an example for the reconstruction process in the future so that the reconstruction process will not only be an effort to fulfill residential needs for disaster victims but also an effort to preserve local architecture which is a container of local culture and form of community response to the condition environment in an area.